Bipolar I and bipolar II subtypes in older age: Results from the Global Aging and Geriatric Experiments in Bipolar Disorder (GAGE‐BD) project. (23rd November 2022) - Beunders, Alexandra J. M.; Klaus, Federica; Kok, Almar A. L.; Schouws, Sigfried N. T. M.; Kupka, Ralph W.; Blumberg, Hilary P.; Briggs, Farren; Eyler, Lisa T.; Forester, Brent P.; Forlenza, Orestes V.; Gildengers, Ariel; Jimenez, Esther; et al.
Abstract: Objectives: The distinction between bipolar I disorder (BD‐I) and bipolar II disorder (BD‐II) has been a topic of long‐lasting debate. This study examined differences between BD‐I and BD‐II in a large, global sample of OABD, focusing on general functioning, cognition and somatic burden as these domains are often affected in OABD. Methods: Cross‐sectional analyses were conducted with data from the Global Aging and Geriatric Experiments in Bipolar Disorder (GAGE‐BD) database. The sample included 963 participants aged ≥50 years (714 BD‐I, 249 BD‐II). Sociodemographic and clinical factors were compared between BD subtypes including adjustment for study cohort. Multivariable analyses were conducted with generalized linear mixed models (GLMMs) and estimated associations between BD subtype and (1) general functioning (GAF), (2) cognitive performance (g‐score) and (3) somatic burden, with study cohort as random intercept. Results: After adjustment for study cohort, BD‐II patients more often had a late onset ≥50 years ( p = 0.008) and more current severe depression ( p = 0.041). BD‐I patients were more likely to have a history of psychiatric hospitalization ( p < 0.001) and current use of anti‐psychotics ( p = 0.003). Multivariable analyses showed that BD subtype was not related to GAF, cognitive g‐score or somatic burden. Conclusion: BD‐I and BD‐II patients did not differ in terms of general functioning, cognitive impairment or somatic burden. Some clinical differences were observed between the groups, which could be the consequence of diagnostic definitions. The distinction between BD‐I and BD‐II is not the best way to subtype OABD patients. Future research should investigate other disease specifiers in this population.